Soil - Geosynthetic inclined plane shear behavior: Influence of soil moisture content and geosynthetic type - Maria de Lurdes Lopes (2014)
This paper deals with the inclined plane shear on three different geosynthetics (a geocomposite (GC), a non-woven geotextile (GTX), and an extruded geogrid (GGR)) with a residual soil from granite. Soil and geosynthetic properties, test equipment, and procedures are described. The influence of soil moisture content and geosynthetic type on soil - geosynthetic interaction behavior is discussed by analyzing the results of the inclined plane shear tests. The main conclusions that can be outlined from the present study are the following: (1) the influence of soil moisture content was relevant for the soil - GTX and soil - GC interfaces. Indeed, the resistance of those interfaces decreased with the increase of soil moisture content. No significant differences were observed between the behavior of those geosynthetics; (2) the influence of soil moisture content on the behavior of the soil - GGR interface was less evident. A slight decrease on the interface friction angle was only observed for the highest soil moisture content; (3) the dry soil - GGR interface resistance was lower than that observed for the other two geosynthetics due to the relevance of soil - soil friction at the GGR apertures, to the high percentage of fines of the soil used in the research (D50=1·00 mm), and to the smoother solid lateral surface of the extruded GGR when compared with the surface of the GTX or GC. (c) 2014 W. S. Maney & Son Ltd.